Pemberdayaan Industri Rumahan Gula Merah Berbasis Ekonomi Kreatif di Desa Cipaku Kecamatan Mrebet Kabupaten Purbalingga - Muhamad Maulana Ikhsanul Khafidli (JEPEmas: Jurnal Pengabdian Masyarakat (Bidang Ekonomi), 2023)
The definition of empowerment has been put forward by many experts. When viewed from the root word, "daya" is a basic word and is added by the prefix "ber", which means having power. Power is the same as power/strength, so the meaning of the word empowered is to have power/strength. Empowerment can be interpreted as an effort made so that the object becomes empowered or has power. The community is a large number of people who live in the same area, besides that other experts define the community as people who interact in a certain area and have a common culture (John J. Macionis, 1997). The community is an important actor who has a position as an active constructive actor, not just a passive recipient. Empowering the community aims so that the community is able to recognize their needs, formulate plans and carry out development independently